68 AMINOGUANIDINE, A SELECTIVE INHIBITOR OF INDUCIBLE NITRIC OXIDE SYNTHASE PREVENTS MALE GERM CELL APOPTOSIS AFTER HORMONE DEPRIVATION. (10th December 2015) - Nuñez, C.; Vera, Y.; Castanares, M.; Atienza, V.; Lue, Y.; Wang, C.; Swerdloff, R. S.; Hikim, Sinha A.P.
Abstract : Several lines of evidence indicate that increased nitric oxide (NO) production through up-regulation of inducible nitric oxide synthase (iNOS) plays a major role in the induction of apoptosis in various cell systems, including male germ cells. In earlier studies, using murine models of testicular hyperthermia or hormone deprivation, we have shown that the mitochondria-dependent (intrinsic) pathway signaling is essential for male germ cell apoptosis. In a recent study, we have also documented the involvement of NO-mediated intrinsic pathway signaling in male germ cell apoptosis. To further explore the role of iNOS in regulating testicular germ cell apoptosis, in the present study, we examined whether a selective iNOS inhibitors could prevent or attenuate hormone deprivation-induced germ cell death. Groups of 5 adult (60 days old) male SD rats received one of the following treatment daily for 5 days: i) a sc injection of gonadotropin-releasing hormone antagonist (GnRH-A), ii) an ip injection of saline as a vehicle control, and iii) GnRH-A + ip injections of 100, 250, or 500 mg/kg BW of aminoguanidine. Rats were killed 5 days after treatment. Germ cell apoptosis was detected by TUNEL assay and quantitated as number of apoptotic germ cells per 100 Sertoli cells at stages VII-VIII. GnRH-A treatment for 5 days led to a significant (P ≤0.001) increase (100.4 ± 10.2) in the mean incidence of germ cell apoptosis exclusively at stages VII-VIII, when compared to controls, where no apoptosis was detected. Concomitant administration of aminoguanidine at all dose levels (100, 250, and 500 mg/kg BW) significantly (P ≤0.001 prevented GnRH-induced germ cell apoptosis by 61.7%, 58.6%, and 67.9%, respectively and fully prevented PARP cleavage. Taken together, these results further illustrates the importance of the NO-mediated signaling pathway in regulating germ cell apoptosis and suggest that inhibition if iNOS may provide a new therapeutic option in preventing acute testicular injury associated with increased germ cell apoptosis. Supported by NIH grants HD 39293 and GM 08683.